Total hip replacement in a black hip: a case report and review of literature - Shah, Vikram; Pachore, Javahir; Patil, Jayesh; Gujjar, Pranay; Sinha, Amit Kumar (International Journal of Research in Orthopaedics, 2023)
Alkaptonuria is a rare metabolic disease leading to the accumulation of a blue-black pigment namely homogentisic acid in the cartilaginous tissue and body fluids giving them a black color. It is an autosomal recessive disease due to the deficiency of the hepatic enzyme oxidase which results in the accumulation of homogentisic acid in the skin, cartilage, and collagenous tissue giving them a black color. Herein we report a case of 65 years old gentleman who presented to our emergency department post domestic fall on his left hip, after which pain and swelling developed around the left hip and he was unable to bear weight with restricted mobility around the same.